The Influence of International and Islamic Law on Labor Laws in Indonesia and Morocco - Muhammad Maksum; Yayuk Afiyanah (Jurnal Cita Hukum, 2022)
Work agreements between workers and employers form the basis for determining rights and obligations. Employment agreements are influenced by the laws governing a country and its historical experience. This study aims to analyze the influence of international and Islamic law on labor law in two countries, both Indonesia and Morocco. The research method used is a qualitative research method with a comparative approach. The results of the study stated that by comparing the provisions of work agreements from three sources of law, namely Indonesian, Moroccan, and Islamic law, it was found that international law had an effect on national law. Islamic law has little effect on work agreements. The influence of Islamic law is found more in Moroccan regulations than in Indonesian regulations. Several different concepts regulated in the source of law include the concept of work agreements, restrictions on the age of children who can enter into work relationships, the object or work employed, and the designation of work areas. This research has implications for the openness of international work transactions or the acceptance of foreign workers due to the same arrangement although with certain restrictions according to a country's policy.